Phaeocystis antarctica blooms strongly influence bacterial community structures in the Amundsen Sea polynya - Delmont, Tom O.; Hammar, Katherine M.; Ducklow, Hugh W.; Yager, Patricia L.; Post, Anton F. (Frontiers in Microbiology, 2014)
Rising temperatures and changing winds drive the expansion of the highly productive polynyas (open water areas surrounded by sea ice) abutting the Antarctic continent. Phytoplankton blooms in polynyas are often dominated by the haptophyte Phaeocystis antarctica, and they generate the organic carbon that enters the resident microbial food web. Yet, little is known about how Phaeocystis blooms shape bacterial community structures and carbon fluxes in these systems. We identified the bacterial communities that accompanied a Phaeocystis bloom in the Amundsen Sea Polynya during the austral summers of 2007-08 and 2010-11. These communities are distinct from those determined for the Antarctic Circumpolar Current and off the Palmer Peninsula. Diversity patterns for most microbial taxa in the Amundsen Sea depended on location (e.g., waters abutting the pack ice near the shelf break and at the edge of the Dotson glacier) and depth, reflecting different niche adaptations within the confines of this isolated ecosystem. Inside the polynya, P. antarctica coexisted with the bacterial taxa Polaribacter sensu lato, a cryptic Oceanospirillum, SAR92 and Pelagibacter. These taxa were dominated by a single oligotype (genotypes partitioned by Shannon entropy analysis) and together contributed up to 73% of the bacterial community. Size fractionation of the bacterial community (<3 µm (free-living bacteria) versus >3 µm (particle-associated bacteria)) identified several taxa (especially SAR92) that were preferentially associated with Phaeocystis colonies, indicative of a distinct role in Phaeocystis bloom ecology. In contrast, particle-associated bacteria at 250 m depth were enriched in Colwellia and members of the Cryomorphaceae suggesting that they play important roles in the decay of Phaeocystis blooms.A